The Uruguay Round and international trade in agricultural products: implications for Arab countries - Goldin, Ian; Kherallah, Mylene (International Monetary Fund, 1996)
This chapter reviews the agricultural trade provisions of the Uruguay Round, assesses their likely consequences for international trade and their impact on agricultural prices with reference to the Arab countries. It includes country analyses for: Algeria, Saudi Arabia, Egypt, Morocco, Tunisia, Jordan, the Syrian Arab Republic, Somalia, and Sudan.